The Wall Street Journal guide to the end of Wall Street as we know it : what you need to know about the greatest financial crisis of our time-- and how to survive it - Kansas, Dave. (New York : Collins Business, 2009)
We're in the midst of the greatest financial crisis of our time. Do you know what really happened? Are you prepared for what's to come?
"More risk is simply more profit" -- Financial wizardry -- Canaries -- Tsunami -- The new world order -- What is safe? -- Debt and destruction -- On investment strategy.
Keywords: Investments -- United States; Stocks -- United States; Finance -- United States; Stock exchanges; Financial crises -- United States